Hyperendemic rheumatic heart disease in a remote Australian town identified by echocardiographic screening. Issue 3 (6th July 2020) - Francis, Joshua R; Fairhurst, Helen; Hardefeldt, Hilary; Brown, Shannon; Ryan, Chelsea; Brown, Kurt; Smith, Greg; Baartz, Roz; Horton, Ari; Whalley, Gillian; Marangou, James; Kaethner, Alex; et al.
Abstract: Objectives: Using echocardiographic screening, to estimate the prevalence of rheumatic heart disease (RHD) in a remote Northern Territory town. Design: Prospective, cross‐sectional echocardiographic screening study; results compared with data from the NT rheumatic heart disease register. Setting, participants: People aged 5–20 years living in Maningrida, West Arnhem Land (population, 2610, including 2366 Indigenous Australians), March 2018 and November 2018. Intervention: Echocardiographic screening for RHD by an expert cardiologist or cardiac sonographer. Main outcome measures: Definite or borderline RHD, based on World Heart Federation criteria; history of acute rheumatic fever (ARF), based on Australian guidelines for diagnosing ARF. Results: The screening participation rate was 72%. The median age of the 613 participants was 11 years (interquartile range, 8–14 years); 298 (49%) were girls or women, and 592 (97%) were Aboriginal Australians. Definite RHD was detected in 32 screened participants (5.2%), including 20 not previously diagnosed with RHD; in five new cases, RHD was classified as severe, and three of the participants involved required cardiac surgery. Borderline RHD was diagnosed in 17 participants (2.8%). According to NT RHD register data at the end of the study period, 88 of 849 people in Maningrida and the surrounding homelands aged 5–20 years (10%) were receiving secondary prophylaxis following diagnoses of definite RHD or definite or probable ARF. Conclusion: Passive case finding for ARF and RHD is inadequate in some remote Australian communities with a very high burden of RHD, placing children and young people with undetected RHD at great risk of poor health outcomes. Active case finding by regular echocardiographic screening is required in such areas.